INTEGRATION OF ISLAMIC VALUES INTO THE NATIONAL EDUCATION CURRICULUM - Firmansyah; Fahrina Yustiasari Liriwati; Zulhimma; Iyad Abdallah Al- Shreifeen (International Journal of Teaching and Learning, 2024)
Education plays an important role in shaping strong character and values in future generations. In an increasingly complex and globally connected environment, the challenge of upholding Islamic values is becoming increasingly relevant. Therefore, the integration of Islamic values into the national educational curriculum has become a major focus in efforts to shape religious attitudes in students. This research study uses a literary study which takes literature that matches the context of the research to be studied. The findings of this study see that integrating Islamic values can help prevent erosion of religious attitudes in students. In an era of globalization, students are often exposed to various cultural influences and values that are contrary to religious teachings. Therefore, the integration of Islamic values into the curriculum provides a strong moral and ethical foundation for students. The approaches used in this integration include specialized teaching of the teachings of Islam, the use of learning methods involving Islamic values, as well as the development of a character curriculum based on the values of Islam. With a combination of these approaches, students are expected to be able to understand, internalize, and apply Islamist values in everyday life.